PSO optimized PI controlled DC‐DC buck converter‐based proton‐exchange membrane fuel cell emulator for testing of MPPT algorithm and battery charger controller. (17th December 2020) - Premkumar, K.; Vishnupriya, M.; Thamizhselvan, T.; Sanjeevikumar, P.; Manikandan, B.V.
Summary: In this article, particle swarm optimized proportional integral (PI) controlled DC‐DC buck converter‐based proton‐exchange membrane fuel cell emulator has been proposed to test the maximum power point tracking algorithm and battery charging controller. Particle swarm optimization is used to optimize the proportional gain (Kp ) and integral gain ( K i ) of the proportional integral controller for emulating the characteristics of the PEM fuel cell. The simulation model of the proposed PEM fuel cell emulator is created and tested using MATLAB Simulink package. To validate the effectiveness of the proposed PEM fuel cell emulator, it is tested under different operating conditions. The polarization characteristics of the PEM fuel cell emulator are compared with PEM fuel cell reference model. The suitability of the PEM fuel cell emulator has been tested with MPPT algorithm and MPPT battery charging controller. Also, real‐time testing of the proposed PEM fuel cell emulator has been realized through experimental set up and the corresponding results are analyzed. Abstract : This research paper deals with design and development of proton‐exchange membrane fuel cell emulator for testing of MPPT algorithm and battery charger controller using PSO optimized PI controlled DC‐DC Buck converter. Particle swarm optimization has been used to optimize the parameter of the PI controller to emulate the exact behavior of the reference fuel cell model. The proposed PSO optimized PI controlled DC‐DC Buck converter‐based proton‐exchange membrane fuel cell emulator provides the successful operation in three regions that are, region of activation polarization, region of ohmic polarization, and region of concentration polarization. The proposed fuel cell emulator has been tested with perturb and observe maximum power point tracking algorithm and constant voltage battery charging control. The developed PEM fuel cell has been tested for different operating conditions such as varying temperature, varying fuel pressure, and varying air pressure conditions. In simulation, the emulation efficiency of the proposed system was 98.1%, the maximum power point ratio of the P&O MPPT algorithm testing was around 95% to 98%, and efficiency of the charger controller was varying from 90% to 98%. The proposed PEM fuel cell emulator has been successfully realized in real time with low cost microcontroller that is, control logic for the PEM fuel cell emulator was implemented using Arduino ATmega board. From the experimental results, emulation efficiency obtained was from 94% to 95%, the maximum power point ratio of the MPPT controller was from 91% to 94%, charging efficiency of the charger controller was varying from 83% to 96.7%. From the simulation and experimental verification results, it has been proved that, the proposed PEM fuel cell emulator deems to be the suitable system for testing any MPPT and charger controller algorithm developed for fuel cell.